2015
DOI: 10.7314/apjcp.2015.16.9.3957
|View full text |Cite
|
Sign up to set email alerts
|

Oral Contraceptives, Abortion and Breast Cancer Risk: a Case Control Study in Saudi Arabia

Abstract: Age at first use of OCPs had no effect on breast cancer risk (p=0.452) or age at diagnosis (p=0.074). Conclusions: Prolonged use of OC (more than 10 years) may be associated with increased risk of breast cancer in Saudi women. Larger population based studies are needed to confirm this finding in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 24 publications
(17 reference statements)
4
17
3
1
Order By: Relevance
“…25 A systematic review of 15 case-control studies and 8 cohort studies found that a history of OC use slightly increases breast cancer incidence (OR 1.08; 95% CI, 1.00–1.17), but the results were no longer significant when only United States-based studies were included (OR 1.03; 95% CI, 0.93–1.14). 26 Two recent case-control studies conducted in Norway 27 and Saudi Arabia 28 both indicated that breast cancer risk increased only if OC use continued for at least 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…25 A systematic review of 15 case-control studies and 8 cohort studies found that a history of OC use slightly increases breast cancer incidence (OR 1.08; 95% CI, 1.00–1.17), but the results were no longer significant when only United States-based studies were included (OR 1.03; 95% CI, 0.93–1.14). 26 Two recent case-control studies conducted in Norway 27 and Saudi Arabia 28 both indicated that breast cancer risk increased only if OC use continued for at least 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established in the literature that changing reproductive patterns including late childbearing, low parity and shorter period of breastfeeding increase the risk of breast Ca [7]. Previous studies have also shown that, prolonged endogenous estrogen exposure owing to early menarche, late age at first delivery and late menopause or exogenous exposure, mainly due to hormone replacement therapy or use of oral contraceptive pills have been associated with breast Ca [8]. The role of certain factors such as spontaneous or induced abortion in the development of breast Ca remains controversial [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…There is a paucity of data regarding HRT from KSA, the only one study undertaken this topic in 2003 and reported a prevalence rate of HRT of 5% [20]. A recent study from KSA have reported long term use of oral contraceptive pills (OCP) in KSA and its association within creased breast cancer risk [21].…”
Section: Discussionmentioning
confidence: 99%